Modulation of van der Waals and classical epitaxy induced by strain at the Si step edges in GeSbTe alloys - Eugenio Zallo (Nature Portfolio, 2017)
Abstract The present work displays a route to design strain gradients at the interface between substrate and van der Waals bonded materials. The latter are expected to grow decoupled from the substrates and fully relaxed and thus, by definition, incompatible with conventional strain engineering. By the usage of passivated vicinal surfaces we are able to insert strain at step edges of layered chalcogenides, as demonstrated by the tilt of the epilayer in the growth direction with respect of the substrate orientation. The interplay between classical and van der Waals epitaxy can be modulated with an accurate choice of the substrate miscut. High quality crystalline GexSb2Te3+x with almost Ge1Sb2Te4 composition and improved degree of ordering of the vacancy layers is thus obtained by epitaxial growth of layers on 3–4° stepped Si substrates. These results highlight that it is possible to build and control strain in van der Waals systems, therefore opening up new prospects for the functionalization of epilayers by directly employing vicinal substrates.